Study of the Effect of Proximate, Ultimate, and Calorific Value Analysis on Methane Gas Emission (CH4) on Combustion of Coal for Sustainable Environment - Reni Arisanti; Maulana Yusuf; M. Faizal (Science and Technology Indonesia, 2018)
Coal is a hydrocarbon fuel consisting of a mixture of substances containing carbon, hydrogen, oxygen, and containing less sulfur and nitrogen. Utilization of coal as fuel, especially in large scale causes methane gas emissions that can increase the impact of global warming, causing a decrease in environmental quality. Methane gas emissions in coal combustion are influenced by coal proximate and ultimate analysis. Proximate analysis includes moisture content, volatile matter, and fixed carbon, while ultimate analysis is carbon, hydrogen and oxygen. This study aims to determine the analysis of the effect of proximate, ultimate, and caloric value of methane emissions in coal combustion. This research is experimental, using quantitative method with descriptive and associative approach. The effect of proximate analysis, the lower the calorific value, the higher content moisture, the time and duration of coal combustion will be longer. Coal 5674 cal / gr, burning time 65 minutes, combustion length 39 minutes, moisture content 14.85%, coal 5747 cal / gr, burning time 60 minutes, duration of burning 31 minutes, moisture content 14.71%, coal 5617 cal / gr, burning time 49 minutes, combustion length 28 minutes, moisture content 12.17%, while coal 6992 cal / gr combustion time 38 minutes, combustion time only 4 minutes, and mosisture content 3.53%. Volatile matter in coal will affect the incubation period, the higher the volatile matter of the incubation period the faster. Coal 5617 cal / g incubation period 21 minutes, volatile matter 39.20%, coal 5674 cal / gr incubation period 26 minutes, volatile matter 38.39%, coal 5747 cal / gr, incubation period 29 minutes, volatile matter 39,30 %. For coal 6992 cal / gr incubation period 34 minutes, volatile matter 18.13%. The effect of ultimate analysis, the higher the carbon content, the higher the fixed carbon content, and the lower the hydrogen, the higher the calorific value of the coal and the less methane gas emissions. While the higher the oxygen content, the more burned the coal will be, the faster the incubation time and the longer burning time, so that the emissions of methane gas out into the atmosphere will be more and more.